In Vitro Assessment of Total Phenolic, Total Flavonoid and Sunscreen Activities of Crude Ethanolic Extract of Belimbing wuluh (Averrhoa bilimbi) Fruits and Leaves - Muhammad Ryan Radix Rahardhian (Journal of Global Pharma Technology, 2016)
Averrhoa bilimbi, namely belimbing wuluh in Indonesia. It’s the fruits used to food in vegetable dishes. Belimbing wuluh’s leaves and fruits are traditional herb in Indonesian. This study aim to determined total phenolic content, total phenolic content and sunscreen activity from ethanolic extract of Belimbing Wuluh fruits and leaves. Total phenolic content of fruits ethanolic extract is 19.8022 ± 1.6696 mg GAE/g more than leaves ethanolic extract 6.5886±0.0590 mg GAE/g. Both have significant differences after tested t test (sig<0.05). Total flavonoid content of fruits ethanolic extract 24.7458±0.3291 mg RE/g more than leaves ethanolic extract 13.3126±0.5695 mg RE/g. Both have significant differences after tested t test (sig<0.05). Sun Protecting Factor of leaves ethanolic extract better than fruits ethanolic extract. Only one leaves ethanolic extract concentration of 300 ppm can be drawn in the total block valuation category with ultra protection. The conclusion is leaves ethanolic extract has good potential as an active sunscreen ingredient although it has a total phenolic content and a lower total of flavonoids than fruits ethanolic extract of belimbing wuluh. These data indicate that the sunscreen active ingredients found on the leaves of belimbing wuluh are suspected of phenolic compounds and other components that have a conjugated double bond that can absorb UV light in the 290-320 nm range.Keywords: Averrhoa bilimbi, Total Phenolic Content, Total Flavonoid Content, Sunscreen Activity.